2009
DOI: 10.1111/j.1567-1364.2008.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of host and vector for high-efficiency transformation and gene disruption inDebaryomyces hansenii

Abstract: Debaryomyces hansenii is one of the most osmotolerant and halotolerant yeasts. The molecular mechanisms underlying its extreme osmotolerance and halotolerance have drawn considerable attention in the recent past. However, progress in this regard has been limited due to lack of availability of a transformation system and molecular tools to study the functions of the genes in D. hansenii. Here, we have described the development of an efficient transformation system for D. hansenii that is based on a histidine au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…This fragment was not seen in two of the eight transformants, suggesting that the URA3 gene might be disrupted by homologous recombination in two of the transformants. The rate of homologous recombination was similar to that reported in a putative xylose reductase gene of D. hansenii (Minhas et al, 2009). The low efficiency of homologous recombination suggested that transforming DNA was predominantly integrated into the D. occidentalis genome by random events.…”
supporting
confidence: 77%
“…This fragment was not seen in two of the eight transformants, suggesting that the URA3 gene might be disrupted by homologous recombination in two of the transformants. The rate of homologous recombination was similar to that reported in a putative xylose reductase gene of D. hansenii (Minhas et al, 2009). The low efficiency of homologous recombination suggested that transforming DNA was predominantly integrated into the D. occidentalis genome by random events.…”
supporting
confidence: 77%
“…This work will be facilitated by genetic tools and other resources that exist for many of the dominant genera that we detected (e.g. Kück and Hoff, 2010; Minhas et al, 2009; Prax et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…A 2.5-kb fragment (corresponding to DhPPZ1 ORF along with its native promoter) was amplified using the forward DhPPZ1_Full F and reverse DhPPZ1_ORF RFPR primers and cloned at Sal1/Xho1 sites in plasmid pDH11 (30) to obtain pAN4. For constructing different N-terminal mutants (pAN51, pAN52, pAN53, pAN54, pAN55, and pAN56) the PCR-based overlap extension method was followed (31).…”
Section: Methodsmentioning
confidence: 99%